Effects of an educational programme on shared decision‐making among Korean nurses. Issue 6 (8th April 2014) - Jo, Kae‐Hwa; An, Gyeong‐Ju
Abstract : This study was conducted to examine the effects of an educational programme on shared decision‐making on end‐of‐life care performance, moral sensitivity and attitude towards shared decision‐making among Korean nurses. A quasi‐experimental study with a non‐equivalent control group pretest–posttest design was used. Forty‐one clinical nurses were recruited as participants from two different university hospitals located in Daegu, Korea. Twenty nurses in the control group received no intervention, and 21 nurses in the experimental group received the educational programme on shared decision‐making. Data were collected with a questionnaire covering end‐of‐life care performance, moral sensitivity and attitude towards shared decision‐making. Analysis of the data was done with the chi‐square test, t ‐test and Fisher's exact test using SPSS/Win 17.0 (SPSS, Inc., Chicago, IL, USA). The experimental group showed significantly higher scores in moral sensitivity and attitude towards shared decision‐making after the intervention compared with the control group. This study suggests that the educational programme on shared decision‐making was effective in increasing the moral sensitivity and attitude towards shared decision‐making among Korean nurses.